2014
DOI: 10.1039/c4cp00461b
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for solvate ionic liquids

Abstract: Certain concentrated mixtures of salts and solvents are not simply "solutions" anymore, but they may be described as "ionic liquids". In this perspective paper, we describe possible criteria for the new family of ionic liquids: "solvate" ionic liquids. This subclass of ionic liquids was originally proposed by Angell et al. in their recent review; however, their criteria remain to be debated. Concentrated mixtures of lithium salts and organic solvents are useful models for these solvate ionic liquids, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
368
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(379 citation statements)
references
References 88 publications
10
368
0
1
Order By: Relevance
“…a application. [1][2][3] Because of their negligible vapor pressure and the resulting low volatility, ionic liquids (ILs) have been presented as a very promising class of new reaction media, since they also offer the possibility of tuning their physicochemical properties such as conductivity, density, melting point, polarity or viscosity, through the combination of a large range of different possible cations and anions. 4 Today, between 300 and 400 different ILs are already commercially available 5 and some of these ILs are well established in new technologies.…”
Section: Rudi Van Eldikmentioning
confidence: 99%
See 1 more Smart Citation
“…a application. [1][2][3] Because of their negligible vapor pressure and the resulting low volatility, ionic liquids (ILs) have been presented as a very promising class of new reaction media, since they also offer the possibility of tuning their physicochemical properties such as conductivity, density, melting point, polarity or viscosity, through the combination of a large range of different possible cations and anions. 4 Today, between 300 and 400 different ILs are already commercially available 5 and some of these ILs are well established in new technologies.…”
Section: Rudi Van Eldikmentioning
confidence: 99%
“…7 On considering possible solvent-solute interactions, the nucleophilicity of ILs plays a crucial role as most of the anions that form part of ILs, e.g. Cl − , Br − , SCN − , NO 3 − or N(CN) 2…”
Section: Rudi Van Eldikmentioning
confidence: 99%
“…[1][2][3] This new subset of ILs, referred to as solvate ILs, has become especially important for preparing metal ion-based ILs, which can be used as a thermally stable electrolyte for energy storage devices. Unlike aprotic ILs and metal salt binary mixtures employed as typical IL-based battery electrolytes, solvate ILs can provide a high concentration of metal ions required for fast electrode reactions in batteries.…”
Section: Introductionmentioning
confidence: 99%
“…117,122 Consequently, solvate ILs are suitable for use as electrolytes in lithium ion batteries [111][112][113][114] and lithium-sulfur batteries. [115][116][117][118][119][120] The most striking and significant findings of our research on solvate ILs are the formation criteria of solvate ILs, 101 the enhanced oxidation stability of coordinating solvents, 95 the low coordinating properties of solvate cations and anions, and their electrode reactions with graphite. 121,122 Figure 8 shows how the anionic structures of lithium salts affect the formation of solvate ILs.…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 99%
“…[89][90][91][92] We explored a variety of such combinations and found that, in certain combinations, these materials have similar properties to conventional aprotic ILs. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] We conclude that these mixtures can be categorized as "solvate ILs," i.e., liquids consisting of a salt and a solvent that strongly coordinates with cations or anions to form stable solvate ions. 110 Detailed studies of the solvate IL on the transport properties, [93][94][95][96][97][98][99] spectroscopic, [99][100][101][102][103] crystallographic, [100][101][102][103] electrochemical, [94][95][96]104,105 quantum mechanical characterizations, [106][107][108]…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 99%